2008
DOI: 10.1055/s-2007-989236
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cardiac Troponin Response in Adolescents Playing Basketball

Abstract: Cardiac troponin release is generally found in adult athletes after continuous-type endurance exercises or sport competitions. The purpose of this study was to investigate whether the physical stress experienced by adolescents while playing basketball, an intense, intermittent-type sport, could induce transient elevations of the serum cardiac troponin T (cTnT) and I (cTnI). Serum cTnT and cTnI levels in 10 male adolescent players (age 15.0 +/- 0.7 yr) were assessed immediately before and at 2, 4 and 24 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 20 publications
3
29
2
1
Order By: Relevance
“…The likely explanation for this discrepancy was the use of a simple pre-post exercise sampling regime in previous work. The current data supports Nie et al [13], in basketball players, and Carranza-García et al [10], in futsal players, who reported an increase in cTn several hours after simulated match. Consequently, our findings show, in line with continuous endurance exercise studies [4,20], the importance of obtained multiple blood samples during recovery to observe the maximum posteffort value.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The likely explanation for this discrepancy was the use of a simple pre-post exercise sampling regime in previous work. The current data supports Nie et al [13], in basketball players, and Carranza-García et al [10], in futsal players, who reported an increase in cTn several hours after simulated match. Consequently, our findings show, in line with continuous endurance exercise studies [4,20], the importance of obtained multiple blood samples during recovery to observe the maximum posteffort value.…”
Section: Discussionsupporting
confidence: 91%
“…For example, available scientific data related to cTn release after intermittent exercise, such as soccer [10,11], rugby [12], basketball [13] or floorball [14] is limited, often poorly controlled [12] and with limited sampling times post-exercise [11,12,14]. Consequently this has produced contradictory data.…”
Section: Introductionmentioning
confidence: 99%
“…The data obtained matched with other researchers' results who reported a decrement in serum inflammatory markers including C reactive protein (CRP) by 25% after 28 days (8,14,19,21,23,26). The potential of skeletal troponin I and hyp as markers of muscle injury may be useful for assessing the effects of intense exercise for soft tissue injuries (31,48,51,55). So, in our study, troponin I and hyp values were measured in the serum of placebo and sumac groups' pre, during and post-exercise test.…”
Section: Discussionsupporting
confidence: 83%
“…The kinetic profile of cTnI and cTnT circulating levels after strenuous exercise in apparently healthy subjects [25,40,[52][53][54][55][56][77][78][79][80][81][82][83][84][85][86][87][88][89][90] is different from that usually observed in patients with AMI. It is well known that circulating levels of cTnI and cTnT in patients with uncomplicated type 1 AMI usually peak between 12 and 36 h from beginning of thoracic pain, gradually returning to below the 99th URL value within 5-7 days [1,3,40,76].…”
Section: Mechanisms Of Troponin Release In Cardiac Patients and Healtmentioning
confidence: 99%